INTEGRITAS MASYARAKAT PLURALISME JALAN TENGAH DWIPOLAR DÂR AL-HARB DAN DÂR AL-ISLÂM : STUDI GEOPOLITIK ISLAM - Ritaudin, M. Sidi (AL-ADYAN, 2010)
The theme of this article is dâr al-harb vis a vis dâr al-Islâm. These issues are usually connected to movement of terorism. At the doctrinal level, thinker Muslims are the followers of those paradigm. So, term jihâd (holy war) in Islamic political was important soul. The interaction of pluralism society in International gathering had bring human being to global society. Throughout the political Islamic thought is evident disposed to those dwiupolar paradigm. Straightaway the question remarks it’s relevance to political contemporary map. According to global society, the map of geopolitic, therefore, it is a challenge for tolerant and pluralism perspective.